PEMBERIAN KOMPOS PADA MEDIA ALLUVIAL TERHADAP PERTUMBUHAN STEK BATANG PURI (Mitragyna speciosa Korth) - Fancora, Timur; AM, Iskandar; Ardian, Hafiz (JURNAL HUTAN LESTARI, 2017)
Puri (Mitragyna speciosa Korth) is one of the plant species in Indonesia forest area which has a high economic value. especially in Kapuas Hulu has been exploited extensively by the community by taking the leaves of the puri that grows naturally in the forest. This research aims to determine the results of composting on alluvial soil as a medium for the growth of stem cuttings of puri. This research was conducted for 10 weeks. The method was Completely Random Design, which consisted of 5 treatment with 10 replication. Each treatment consisted of alluvial without compost, alluvial 4 + compost 1, alluvial 3 + compost 2, alluvial 2 + compost 3, alluvial 1 + compost 4. The variables observed were live percentage, number of shoots, number of leaves, number of roots and length of roots. The results showed that adding compost on stem cuttings of puri at alluvial 4 + compost 1 had a significant effect on the growth parameter of the number leaves, a number of roots and a very significant effect on the parameter of the length of roots. The percentage growth of stem cuttings of puri was 52% Keywords: Compost, Mitragyna species Korth, Stem Cuttings of Puri